2013
DOI: 10.1002/jssc.201300010
|View full text |Cite
|
Sign up to set email alerts
|

Performance of hydrophobic interaction ligands for human membrane-bound catechol-O-methyltransferase purification

Abstract: Despite of membrane catechol-O-methyltransferase (MBCOMT, EC 2.1.1.6) physiological importance on catecholamines' O-methylation, no studies allowed their total isolation. Therefore, for the first time, we compare the performance of three hydrophobic adsorbents (butyl-, epoxy-, and octyl-Sepharose) in purification of recombinant human COMT (hMBCOMT) from crude Brevibacillus choshinensis cell lysates to develop a sustainable chromatographic process. Hydrophobic matrices were evaluated in terms of selectivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 30 publications
(70 reference statements)
1
23
0
Order By: Relevance
“…Interestingly, from the ligands in study, octyl was found to be the most selective for MBCOMT purification over butyl and epoxy, probably due to its higher hydrophobicity and long chain length, despite MBCOMT is recovered under mild conditions [6]. In particular, it was observed a multiple peak pattern for MBCOMT elution that may be related to amino acids that are responsible for the interaction with the stationary phase [6]. Specifically, if the target protein binds to the matrix with the highly hydrophobic amino acids present in the MBCOMT membrane anchor region, higher detergent concentrations will be required for elution than other less hydrophobic MBCOMT regions [6].…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Interestingly, from the ligands in study, octyl was found to be the most selective for MBCOMT purification over butyl and epoxy, probably due to its higher hydrophobicity and long chain length, despite MBCOMT is recovered under mild conditions [6]. In particular, it was observed a multiple peak pattern for MBCOMT elution that may be related to amino acids that are responsible for the interaction with the stationary phase [6]. Specifically, if the target protein binds to the matrix with the highly hydrophobic amino acids present in the MBCOMT membrane anchor region, higher detergent concentrations will be required for elution than other less hydrophobic MBCOMT regions [6].…”
Section: Introductionmentioning
confidence: 91%
“…In particular, it was observed a multiple peak pattern for MBCOMT elution that may be related to amino acids that are responsible for the interaction with the stationary phase [6]. Specifically, if the target protein binds to the matrix with the highly hydrophobic amino acids present in the MBCOMT membrane anchor region, higher detergent concentrations will be required for elution than other less hydrophobic MBCOMT regions [6]. Nevertheless, despite MBCOMT was isolated from a complex lysate, it was recovered without biological activity (unpublished data).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations